2019
DOI: 10.24188/recia.v11.n1.2019.707
|View full text |Cite
|
Sign up to set email alerts
|

Clasificación de los sistemas de producción y grado de impacto ambiental de las pisciculturas en el estado de Amazonas, Brasil

Abstract: A piscicultura é umas atividades zootécnicas que mais tem crescido nos últimos anos, em especial na Amazônia Brasileira. O presente estudo foi realizado no Estado do Amazonas, um dos maiores consumidores de pescado no Brasil. O estudo foi realizado com objetivo de caracterizar os sistemas de produção, o grau de severidade de impactos ambientais que essa atividade promove nos ambientes amazônicos e as perspectivas de desenvolvimento futuro nas diferentes mesorregiões do estado. As investigações foram realizadas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In this study, the juvenile A. gigas were from the natural reproduction of breeding stock raised in ponds and river dam, and were collected directly from the cultivation facilities. These types of breeding structures are used by 93.33% of fish farms in the state of Amazonas and, in the municipality of Manacapuru, only one fish farm has the capacity to produce half a million juvenile A. gigas per year, while another can produce juvenile A. gigas, C. macropomum and B. amazonicus up to a quantity of 2 million for the three species (Lima et al, 2019). In the seven fish farms evaluated in this study, 2,500 to 3,000 juvenile A. gigas were produced by spawning, with the breeding stock kept isolated and/or maintained with other fish species, at a ratio of males to females of 1:1 and 3:2.…”
Section: Parasitementioning
confidence: 99%
“…In this study, the juvenile A. gigas were from the natural reproduction of breeding stock raised in ponds and river dam, and were collected directly from the cultivation facilities. These types of breeding structures are used by 93.33% of fish farms in the state of Amazonas and, in the municipality of Manacapuru, only one fish farm has the capacity to produce half a million juvenile A. gigas per year, while another can produce juvenile A. gigas, C. macropomum and B. amazonicus up to a quantity of 2 million for the three species (Lima et al, 2019). In the seven fish farms evaluated in this study, 2,500 to 3,000 juvenile A. gigas were produced by spawning, with the breeding stock kept isolated and/or maintained with other fish species, at a ratio of males to females of 1:1 and 3:2.…”
Section: Parasitementioning
confidence: 99%
“…74,82,83 Intensive pond production of tambaqui is the most profitable system, but because it depends on intrinsic regional conditions-including weather, prices of agricultural inputs and market conditions, including the currency exchange rate-it may experience peaks and troughs in yield and profitability. 79,80,84 Pedroza Filho et al 85 Characterizing the production system of tambaqui requires considering aspects inherent to regional climatic differences and the high degree of adaptability of tambaqui, which, with the exception of southern-most regions of South America, can be produced at commercial scale with technical-economic feasibility. Such aspects led tambaqui to place second in the ranking of national production and first position among native fish, contributing significantly to the development of Brazilian aquaculture.…”
Section: Farming and Produc Tion Sys Temsmentioning
confidence: 99%
“…Current tambaqui farming practices aim at higher productivity with minimal environmental impact, relying on mathematical models to support decision‐making in farm management 74,82,83 . Intensive pond production of tambaqui is the most profitable system, but because it depends on intrinsic regional conditions—including weather, prices of agricultural inputs and market conditions, including the currency exchange rate—it may experience peaks and troughs in yield and profitability 79,80,84 . Pedroza Filho et al 85 reported that cage farming of tambaqui is on the rise in the northern Brazilian states of Tocantins (TO), Pará (PA) and Mato Grosso (MT), where large, multiple‐use, nearly pristine reservoirs, which may yield quality fish (notably devoid of off‐flavour), are readily available for fish culture operations.…”
Section: Farming and Production Systemsmentioning
confidence: 99%